Ethical Monotheism : a Philosophy of Judaism - Benor, Ehud (Routledge Jewish studies series., 2018)
"The term Ethical Monotheism is an important marker in Judaism's tumultuous transition into the modern era. The term emerged in the context of culture-wars concerning the question of whether or not Jews could or should become emancipated citizens of modern European states. It appeared in arguments whether or not Judaism could be considered a Religion of Reason--a symbolic, motivational representation of a universal morality, and in debates about whether or not Judaism could or should reform itself into a Religion of Reason. This book is both a decisive departure from such discussions and an attempt to add a further, post-modern, statement to their ongoing development. As departure, it refuses to take for granted a philosophical conception of Religion of Reason as the standard for Ethical Monotheism according to which Judaism was to be evaluated or reformed. As continuation, the book undertakes a phenomenology of Jewish modes of ethical religiosity that allows it to inquire what kind of ethical monotheism Judaism might be. Through sophisticated analysis of select "snapshots," or "fragments of a hologram," guided by a robust theory of religion, the author discloses Judaic ethical monotheism as an ongoing wrestling with the meaning of justice. By closely examining five main "snapshots" of this long process--the Bible, rabbinic Judaism, Maimonides, The Zohar, and the modern philosophers, Buber and Levinas--the author offers his own constructive philosophy of Judaism and his own distinctive philosophy of religion"--